ESSENTIALISM AND ENVIRONMENTAL CRISIS: AN INEVITABLE (RE)INTRODUCTION (Romanian Journal of Analytic Philosophy, 2025)
Recent conversations in environmental studies tilt towards the imperative for local knowledge systems. This knowledge is often held by non-experts and outside formal institutional settings. Lived experiences offer alternative perspectives on environmental crises. The challenge, however, remains: how might alternate knowledge be integrated into broader environmental action conversations? In response, metaphysical coherentism, according to which reality consists of a network of independent elements, where every component is grounded in relation to others, is proposed. Such grounding could accommodate the plurality of perspectives that are inherent in the environmental crisis and address the top-down approach in policy frameworks. Metaphysical coherentism argues that greater clarity is needed in the ontological categories of environmental studies.
Keywords: essentialism; environmental crisis; alternate knowledge; metaphysical coherentism; epistemological pluralism